PENGENALAN BAHASA DAERAH LUBUKLINGGAU DILENGKAPI DENGAN TEXT TO SPEECH BERBASIS ANDROID (STUDI KASUS DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA LUBUKLINGGAU) - Lukman Sunardi; Davit IRawan; Indah Pratami (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
A well- Indonesia is an archipelagic country that has many ethnic groups, cultures and languages. Almost all regions in Indonesia have their own regional languages. However, currently the use of regional languages ​​has begun to decline as a means of daily communication in the regions. The accent only looks harsher, you could also say it's rough, even though actually the lubuklinggau accent is soft for lubuklinggau people. Lubuklinggau language is the language that is often used by the people of Lubuklinggau city for daily communication. For this reason, there are many studies discussing technology that can help expand learning about regional languages, especially Lubuklinggau language with features that can be entered into smartphones, namely text-to-speech, typing words and the most important thing is speech recognition. The writers of this study made use of the research technique known as qualitative research. To understand human or social phenomena, qualitative research is a process of research that involves the creation of a comprehensive and complex picture that can be presented in words, the reporting of detailed views obtained from informant sources, and the carrying out of research in its natural settings. The selection of this qualitative research is also due to the fact that the data is more in the nature of information or explanations that are not numerical in nature. Primary data, which are presented in the form of speech or behaviour witnessed through surveillance or conversations, and secondary data, which are presented in the form of literature, make up the data in this investigation. The application produced is an online regional language dictionary application based on Android.